The Influence of NaOH Activator Concentration on the Synthesis of Activated Carbon from Banana Peel for Pb(II) Adsorption - Abdul Hamid; Zeni Rahmawati; Mohammad Abdullah; Tri Esti Purbaningtyas; Faizatur Rohmah; Ike Dayi Febriana (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
Lead has been known as one of the heavy metals with a high adverse effect to the environment and human health. This study reports the activity of activated carbon from biomass of banana peel as an adsorbent to resolve the hazardous lead-contaminated wastewater. The influence of the activator was studied via the alteration of NaOH concentration from 1, 3, and 5 M, where the sample was denoted as AC-1, AC-3, and AC-5. Some techniques, including FTIR, XRD, and SEM were applied to characterize the sample with the highest adsorption capacity. FTIR result affirmed the presence of hydroxyl group on the activated carbon with NaOH 1 M (AC-1) that was beneficial for adsorption. XRD and SEM confirmed that the activated carbon possessed crystalline and amorphous phases with sheet-like morphology. Regarding Pb(II) adsorption, the higher concentration of activator caused the decline of adsorption capacity as the contact time prolonged. The highest adsorption capacity and efficiency were obtained using 1 M NaOH activator with a contact time of 1 hour, which was 3.71 mg/gram and 97.86%, respectively.